How Dense Would the Little Prince’s Planet be? - Curaudeau, Manon (Journal of Interdisciplinary Science Topics, 2017)
In the eponymous book by Antoine de Saint-Exupéry, the Little Prince claims he has watched 44 sunsets in a day. In this paper, this piece of information is used to determine his planet's radius, mass, volume, and density. Using a value of 24 min per sunset, it was estimated that the Little Prince’s planet radius, mass, volume, and density are 5625.60 m, 4.65x1018 kg, 7.458x1011 m3 and 6.235x106 kg m-3 respectively. This would mean that the Little Prince’s planet is 276 times denser that Osmium, the densest element on Earth.